Severe Head Injuries - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical predictors of severe head trauma in 55 children, 1 to 15 years of age, were compared with CT scan findings at the Dept of Pediatrics, Medical College of Wisconsin and Children’s Hospital of Wisconsin, Milwaukee, WI.